Research Methods for Visual Comfort Study - Denan, Zuraini (IIUM Press, 2015)
Research method in visual comfort area developed from a general to a more specific framework: from a consideration of window and lighting of office buildings in general to the specific daylight assessment of an experimental office. The investigation is divided into 4 parts: the survey-questionnaire, the field measurement, the subjective assessment under controlled daylight experiment and the advanced lighting calculation (computer simulation). This paper describes each method of data collection, the equipment used, and limitations.